Strategy for Implementing Risk Management for Gold Pawn Products At PT. Bank Syariah Indonesia Regional Office II Medan - Ucie Fitria Pertiwi Nasution; Sugianto Sugianto (Yayasan Rahmat Islamiyah, 2021)
This study aims to determine the forms of risk of gold pawn products and the implementation of risk management of gold pawn products at PT. Bank Syariah Indonesia Regional Office II Medan. This study uses a qualitative method with a descriptive approach. Data collection techniques were carried out by interview and document study. Data sources come from primary data and secondary data.The results of this study indicate that there are three crucial risks to the gold pawn product at PT. Bank Syariah Indonesia Regional Office II Medan namely market risk, operational risk, and credit/financing risk. The implementation of risk management for gold pawn products at PT. Bank Syariah Indonesia Regional Office II Medan is carried out in several stages, namely risk identification, risk measurement, risk monitoring, and risk control, in accordance with Financial Services Authority Regulation (POJK) No.65/POJK.03/2016 regarding The Implementation of Risk Management For Islamic Commercial Banks and Sharia Business Units in which PT. Bank Syariah Indonesia Regional Office II Medan has carried out these stages to the maximum to deal with the risks that exist in the gold pawn product.